Effects of secretome from dynamic 3D cell culture system onto growth and cytoprotection of nasal fibroblast - Siti NI,; Kavireshna K,; Zafirah MR,; Foo, Yi W; Rabiatul Adawiyah R,; Salina Husain,; Mohd-Ilham A,; Yogeswaran Lokanathan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Three dimensional (3D) models mimic the features of native tissue environment. Thus, morphology and signalling of cells from 3D culture are often more physiological than routine two dimensional (2D) cell culture. It is also known that the cell-secreted products have paracrine effect on other cells growth. In this experimental study, we optimised the nasal fibroblast culture on a 3D cell culture system and studied the effects of secretome from the 3D culture (3DCM) onto fibroblast growth and cytoprotection. Nasal fibroblast was isolated from human nasal turbinates. The suitable microcarrier was selected by culturing the fibroblasts in passage 3 on various types PolyGEM™ polystyrene microcarriers. Then, the cells were cultured on selected microcarrier using a 3D culture system and the conditioned medium (CM) was collected. 3DCM were supplemented to fibroblasts to study for attachment, proliferation, and cytoprotective effects against cytotoxicity of Centella asiatica. Bicinchonic Acid Assay (BCA) was performed to quantify protein amount in CMs. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) was performed for preliminary profiling and comparison of 2DCM and 3DCM protein profile. Our study showed that the 3DCM did not significantly enhance cell attachment and proliferation. The secretome of both 2DCM and 3DCM found to have significant cytoprotective effect onto nasal fibroblast against cytotoxicity of C.asiatica extract. 3DCM had higher protein concentration than 2DCM. SDS-PAGE showed three exclusive proteins in 3DCM and four exclusive proteins in 2DCM. Future study should be conducted on utility of nasal fibroblast secretome on cytoprotection against harmful agents in environment and cytotoxicity of natural products.